PENGARUH SUHU MUKA LAUT TERHADAP AWAL MASUK MUSIM HUJAN DI WILAYAH UTARA-TIMUR ACEH - Yopi Ilhamsyah; Ulfa Mahera; Citra Oktavina (Program Studi Magister Pengelolaan Sumberdaya Alam dan Lingkungan Universitas Almuslim, 2023)
Aceh is a province located in the westernmost part of the Indonesian archipelago and surrounded by waters, located in a tropical area that receives the most solar radiation. The condition of the Aceh region which is mountainous and has valleys results in different and varied rainfall patterns. The sea is a more important role than the land in the process of rain. Where some have concluded that sea surface temperature (SST) and rainfall have a relationship. Therefore, it is necessary to conduct research on the relationship between SST and the onset of the rainy season and the characteristics of rainfall in the North- East region of Aceh. The purpose of this research study is to obtain information on the effect of SST and rainfall in the North-East region of Aceh. The method used in this research is correlation analysis. Based on the results of data analysis in the North-East region of Aceh, the rainfall pattern in the North-Eastern region of Aceh is monsoon type with little influence from the equatorial. The correlation between rainfall and SST anomalies shows different values in each region. The results of the correlation analysis of the onset, the highest occurred in the Banda Aceh with a value of 0,1495 which occurred in the 25th dekad and the length of the rainy season lasted for the 12th dekad. Meanwhile, the lowest occurred in East Aceh district, i.e., 0,0278 which occurred in the 24th dekad with the length of the rainy season last for 13 dekad.